L’héritage de Tristan Tzara a Moïnești - ROBCIUC, Vasile (Studia Universitatis Babeș-Bolyai Dramatica, 2016)
Tristan Tzara’s Heritage in Moineşti. This paper tries to underline the echoes of Tristan Tzara’s work in his birth town: Moineşti, Romania. The author presents the Literary and Cultural Association “Tristan Tzara” and also the Tristan Tzara Notebooks, a series of volumes about Tristan Tzara and Dadaism, with papers written by important scholars. Afterwards, the focus is put on some musical compositions inspired by the life and work of Tristan Tzara.